Criminología y género en el Sistema económico del Ecuador - Vanegas León, Brenda Cielaika (2024)
The objetive of this paper to encourage the incorporatlon of the gender perspective into criminological research made in Ecuador. This research was created from Antonio García- Pablos de Melina and Tania Patricia lbáñez Gómez's documents. In this paper I analyzed the statistics of the prison populaüon with definitions Committee on the Elimination of Discrimination against Women (CEDAW) and Ecuadorlan Constitution. In this artícle demonstrates women· s poverty and socioeconomic conditions are the causes for women become criminal. This research describes the number of women, inequality in payment and work between men and women, the small number of female offenders by lack of interest in gender Criminology on the Economy.